2005
DOI: 10.1152/ajprenal.00019.2005
|View full text |Cite
|
Sign up to set email alerts
|

Vascular ENaC proteins are required for renal myogenic constriction

Abstract: (VSMCs) to contract in response to increases in intraluminal pressure. Although mechanosensitive ion channels are thought to initiate VSMC stretch-induced contraction, their molecular identity is unknown. Recent reports suggest degenerin/epithelial Na ϩ channels (DEG/ENaC) may form mechanotransducers in sensory neurons and VSMCs; however, the role of DEG/ENaC proteins in myogenic constriction of mouse renal arteries has not been established. To test the hypothesis that DEG/ ENaC proteins are required for myog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(177 citation statements)
references
References 47 publications
7
165
5
Order By: Relevance
“…This occurs via dilation or constriction in response to alterations in blood pressure, which incite changes in circumferential wall tension. The active myogenic response closely follows an initial passive distension, as has been observed in a multitude of experimental studies (5,11,19,26,27,30,32,39,45,58,61,63).…”
Section: Vessel Modelsupporting
confidence: 69%
See 1 more Smart Citation
“…This occurs via dilation or constriction in response to alterations in blood pressure, which incite changes in circumferential wall tension. The active myogenic response closely follows an initial passive distension, as has been observed in a multitude of experimental studies (5,11,19,26,27,30,32,39,45,58,61,63).…”
Section: Vessel Modelsupporting
confidence: 69%
“…The active data (5,19,22,26,27,29,64) were subsequently examined to determine the shape and position of the sigmoidal dependence between tension and VSM activation, providing values for C t i and CЈ t i . An iterative bisection method was used for each Strahler order to determine the sigmoidal relationships between MRss and Ttot that, when incorporated into the mathematical system, minimized the error in vessel diameter responses between the model predictions and the experimental results (5,19,22,26,27,29,64).…”
Section: Parameter Determinationmentioning
confidence: 99%
“…In addition, other genes either with or without a heterozygous CFTR genotype could produce the "nonclassic" CF phenotype in the absence of homozygous CFTR mutation as shown previously (Groman et al, 2002). Recently, it was shown that an ENaC gene (SCNN1) produced a non-classical CF phenotype (Sheridan et al, 2005) and ENaC was shown previously to be involved in stretch-induced muscle constriction (Jernigan and Drummond, 2005).…”
Section: Discussionmentioning
confidence: 80%
“…The expressions of ENaC and related acid-sensing ion channel (ASIC) have been demonstrated in cerebral arterial myocytes, and suggested to play a role in MRs (Carattino et al, 2004;Jernigan and Drummond, 2005). However, it is not confirmed in other types arteries, and we could not detect any attenuation of MRs by amiloride (up to 10 M, unpublished data).…”
Section: Epithelial Na + Channel (Enac)mentioning
confidence: 70%